Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/02683555221088373
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of adverse events with sclerosants reported to the United States Food and Drug Administration

Abstract: Objectives To analyze adverse events (AEs) related to sclerosants reported through the Federal Adverse Event Reporting System (FAERS). Methods We queried the FAERS database for all cases associated with sclerosants. Reports were analyzed and stratified based on severity of cases and patient death. Results A total of 1215 cases with 3124 reactions were identified among 4 sclerosants. “General disorder and administration site conditions” reaction group was prevalent in all sclerosants. For polidocanol, deep vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…By contrast, no cases of VTE or death from VTE with the use of STS were reported to this database. 13 The total number of procedures performed in this time period (1970–2021) is unknown, and hence, the absolute frequency of serious adverse events cannot be accurately estimated.…”
Section: Relative Contraindicationmentioning
confidence: 99%
See 3 more Smart Citations
“…By contrast, no cases of VTE or death from VTE with the use of STS were reported to this database. 13 The total number of procedures performed in this time period (1970–2021) is unknown, and hence, the absolute frequency of serious adverse events cannot be accurately estimated.…”
Section: Relative Contraindicationmentioning
confidence: 99%
“…184 There were 7 reports of stroke and 3 reports of TIA recorded in the FAERS database between 1998 and 2021. 13 Most patients have no prior history of TIA or stroke and the most common risk factor is a PFO. Stroke in most cases has been confirmed by ischaemic changes on brain imaging.…”
Section: Relative Contraindicationmentioning
confidence: 99%
See 2 more Smart Citations
“…This sludge was previously isolated by our group and shown to be a complex of apolipoprotein B and fibrinogen. 16 In a recent review of serious adverse events of sclerotherapy reported to the Federal Adverse Event Reporting System (FAERS) database of the U.S. Food and Drug Administration (FDA) in a 51 year period (1970–2021), 17 STS recorded 34 cases of skin necrosis. By contrast, POL had 0 reports of injection site necrosis or skin ulcers, despite having an overall higher number of adverse events reported at 863 cases compared to 312 cases for STS.…”
Section: Risk Factors For Skin Necrosismentioning
confidence: 99%